Accounting Procedures in the Management Processes (Economic journal of Lesya Ukrainka Volyn National University, 2016)
In modern realities accounting may be a function of the management to ensure the control over the processes of planning, implementation and adjustment of plan indicators taking into account the changes in environmental conditions. The priority of different accounting procedures at different stages of the company has been determined. The principles for providing the quality of information have been discovered in order to make effective management decisions. The peculiarities of the financial statements analysis have been shown in order to develop the information base for the management. The systematic approach to the accounting and analytical software management process has been used.
Keywords: accounting and analytical support, administrative processes, managerial accounting, and financial reporting